DIVERGENT CHURCH the bright promise of alternative faith communities. - SHAPIRO, TIM; BRINKERHOFF, KARA; BRINKERHOFF, KARA. (NASHVILLE : ABINGDON PRESS, 2017)
Innovative Christians - engaging in time-honored practices - are creating new types of communities.
Cover; Title; Copyright; Contents; Acknowledgments; Introduction: What Is a Divergent Church?; Chapter 1: Innovation; Chapter 2: What Constitutes a Church?; Chapter 3: Practices; Chapter 4: The Practice of Shaping Community; Chapter 5: The Practice of Conversation; Chapter 6: The Practice of Artistic Expression; Chapter 7: The Practice of Breaking Bread; Chapter 8: The Practice of Community Engagement; Chapter 9: The Practice of Hospitality; Chapter 10: The Voices of Divergent Church Leaders; Chapter 11: Conclusion; Notes; Bibliography
Master record variable field(s) change: 050, 072, 082, 650
Keywords: Christianity -- 21st century; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books; Electronic books